A Hybrid Forecasting System Based on Comprehensive Feature Selection and Intelligent Optimization for Stock Price Index Forecasting - He, Xuecheng; Wang, Jujie (Mathematics (Basel), 2024)
Accurate forecasts of stock indexes can not only provide reference information for investors to formulate relevant strategies but also provide effective channels for the government to regulate the market. However, due to its volatility and complexity, predicting the stock price index has always been a challenging task. This paper proposes a hybrid forecasting system based on comprehensive feature selection and intelligent optimization for stock price index forecasting. First, a recursive feature elimination with a cross-validation (RFECV) algorithm is designed to filter variables that have a significant impact on the target data from multiple datasets. Then, the stack autoencoder (SAE) algorithm is constructed to compress the feature variables. At last, an enhanced least squares support vector machine (LSSVM) algorithm is established to obtain high-precision point prediction results, and the Gaussian process regression (GPR) algorithm is used to obtain reasonable interval prediction results. Taking the Shanghai Stock Exchange (SSE) as an example, the root mean square error (RMSE) and mean absolute percentage error (MAPE) of the model were 6.989 and 0.158%, respectively. In addition, the prediction interval coverage probability (PICP) is 99.792%. Through experimental comparison, the model shows high prediction accuracy and generalization ability.